Main Directorate of the National Police in Kharkiv Region - D. V. Slynko; L. I. Kalenichenko (Bulletin of Kharkiv National University of Internal Affairs)
The scientific study is devoted to the consideration of the legislation process as a form of legal proceedings in the law of ancient Rome. It is noted that in the modern national legal literature, scientific research related to ancient Roman law, as a rule, deals with the problems of substantive law, both civil and family law, and the institutions of procedural law are considered to a much lesser extent. Currently, research on this issue is relevant, since certain institutions and categories of the national legal system are based on the structure of Roman law, its principles, and were developed under its influence. It is emphasised that the legislative form, which was used in private cases in the first half of the Republic, can be considered the first historically developed form of procedure in Roman justice. The procedure was called legislative because it was based, in contrast to the old forms of private self-reprisal, exclusively on the law. It required the parties to act per legis actiones, i.e. without resorting to violence, in a lawful manner, on legal grounds, in a lawful manner. Compliance with the legislative form of legal proceedings guaranteed the legality and formality of the claimant’s (plaintiff’s) claims and the absence of elements of analogy in the claim and provided for the occurrence of only the consequences specified in the law.